Mulberry Leaf and Radix Astragali Regulates Differentially Expressed Genes and Proteins in the Streptozotocin-Induced Diabetic Mice Liver - Shu Zhang (MDPI AG, 2021)
As a chronic non-infectious disease, severely affecting human quality and health of life, diabetes mellitus (DM) and its complications have gradually developed into a major global public health problem. Mulberry Leaf and Radix Astragali have been used as a traditional medicinal formulation in diabetic patients for a long time, whose combination is usually found in traditional Chinese medicine prescriptions. However, due to the unclear synergistic mechanism of them for DM, the changes of differential genes and proteins in the liver tissue of streptozotocin-induced diabetic mice were analyzed, and then the potential synergistic mechanism of them in anti-diabetes was investigated in our research. Compared with the diabetic model group, there were 699 differentially expressed genes and 169 differentially expressed proteins in the Mulberry Leaf and Radix Astragali treated group, and there were 35 common specific genes both in the transcriptome and the proteome. These common genes participated mainly in the pathways, such as retinol metabolism, steroid hormone biosynthesis, and arachidonic acid metabolism. Quantitative real-time PCR() and Western blot results speculated that the synergistic effect on anti-diabetes was mainly through regulating the expression of Tap1, Ncoa4, and Alas2, by down-regulating Fabp2 and Hmox1 and up-regulating Hmgcr, Cyp7a1. All these genes would affect bile acid secretion, alleviate the occurrence of iron death, promote the metabolism and synthesis of glycolipid substances, and ultimately maintain the body’s glucose homeostasis.